1984
DOI: 10.1161/01.res.55.5.609
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic and microvascular responses in the hindquarters during the development of renal hypertension in rats. Evidence for the involvement of an autoregulatory component.

Abstract: SUMMARY. Microvascular responses in the cremaster muscle were compared with changes in mean arterial pressure and hindquarters vascular resistance during the development (initial 3 hours) of two-kidney one-clip renal hypertension in rats, to examine the possibility that an autoregulatory mechanism may contribute to the development of hypertension. Rats were anesthetized with urethane and chloralose and implanted with Doppler flow probes on the renal artery and abdominal aorta. Acute hypertension was produced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1

Year Published

1985
1985
1993
1993

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 34 publications
1
15
1
Order By: Relevance
“…8). Hence, although myogenic responses to the rise in arterial pressure may contribute to the regional vasoconstrictor responses (Meininger et al, 1984), the increase in peripheral resistance may be viewed to involve substantial humorally and/or neurally mediated vasoconstriction.…”
Section: Dcontrol N= 15 Q Right Renal Denervation N=8 I Sham Renal Dementioning
confidence: 99%
“…8). Hence, although myogenic responses to the rise in arterial pressure may contribute to the regional vasoconstrictor responses (Meininger et al, 1984), the increase in peripheral resistance may be viewed to involve substantial humorally and/or neurally mediated vasoconstriction.…”
Section: Dcontrol N= 15 Q Right Renal Denervation N=8 I Sham Renal Dementioning
confidence: 99%
“…Studies by Meininger and colleagues have demonstrated significant autoregulation in the intestinal and hindquarters circulations during acute infusions ofangiotensin II and phenylephrine (5) and during acute renovascular hypertension (3,4) in anesthetized rats. In those studies, the regional circulations were protected at lower pressures while the systemic arterial pressure remained at hypertensive levels.…”
Section: Discussionmentioning
confidence: 99%
“…Autoregulation of blood flow has also been implicated in the genesis of the increased total peripheral resistance in hypertension (1). Recent work demonstrates that autoregulation and the neurohumoral pressor systems are not mutually exclusive, and that autoregulation may interact with neurohumoral vasoconstrictor stimuli to amplify increases in vascular resistance and arterial pressure (2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of blood flow autoregulation in the hind limb skeletal muscle 30 and in the intestine 31 have shown that autoregulation in these regions contributes to the elevated vascular resistance associated with the development of renal hypertension. The renal circulation has been studied extensively in models of hypertension because of the popular theory that abnormal renal function is a prerequisite for the development of hypertension.…”
mentioning
confidence: 99%